Multifacets in silico study of Plant Defensin 1.1 protein (PDF1.1) in Brassica rapa (turnip) - Qudsia Naz; Muhammad Farhan Sarwar; Mudassar Fareed Awan; Sajed Ali; Irfan Mughal; Yousuf Shafiq; Irfan Ahmad (FACETS)
Brassica rapa (turnip) belongs to the Brassicaceae family. Due to the diseases caused by fungal pathogens such as Erysiphe cruciferarum, Alternaria japonica, and Alternaria brassicae, the yield of B. rapa was reduced in many Asian and European countries. Plant defensins (PDFs) are proteins that have antifungal properties. This research aimed to comprehend the key attributes of B. rapa PDF 1.1s by incorporating a wide range of in silico approaches. Initially, we explored orthologues of PDF 1.1 in B. rapa through Blastp in Phytozome v.13 which highlighted fourteen different orthologues. Afterward, by using Mega X, the homology of B. rapa PDF1.1 proteins with Arabidopsis thaliana PDF1.1 proteins was also inferred. While, the results of NCBI CD show that these proteins possessed a common domain, i.e., gamma-thionin. The major findings of this study included the crucial characteristics of PDF1.1 proteins that were explored by utilizing the PANZZER2 web server and BlastKOALA, which proposed that these proteins possessed degradation ability of pathogen’s cells and were also found to be involved in a mitogen-activated protein kinase signaling pathway. Overall, this research provided a better understanding of the crucial contribution of B. rapa PDFs 1.1 under biotic stress specifically, the pathogenic fungal attack.